DISTRIBUSI GAS LPG DENGAN MENCARI RUTE TERPENDEK PERBANDINGAN ALGORITMA DIJKSTRA DAN ANT COLONY WILAYAH KABUPATEN PIDIE - Yuswardi Yuswardi; Balia Balia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Finding the shortest path is a problem finding a path between two nodes with a minimum amount of weight. In the case of finding the shortest path between two different locations on a map, the node will represent the location on the map and the weight represents the time it takes to travel between the two locations. Dijkstra and Ant Colony algorithms are the most commonly used algorithms in the search for the shortest route. Dijkstra and Ant Colony algorithms use greedy principles, which is to find the optimum solution at each step passed, intending to get the optimum solution in the next step that will lead to the best solution at this time to find the shortest route for the distribution of LGP Gas 3 Kg. This problem gave rise to the idea of creating a web-based application, which can search for the shortest route for LPG gas distribution. Where a detailed study of the application of Dijkstra and Ant Colony algorithms is to solve the shortest trajectory problem and the software used is Sublime Text as a script editor, PHP as a programming language, and Google Maps to display maps, and Mysql as a database. This system only displays the shortest distance from the Gas Distribution Company (PT /CV) to the existing Gas bases in Pidie Regency to find out the distance from the initial location to the destination location obtained from Google Maps.Keywords : Dijkstra and Ant Colony Algorithms, Shortest Route Search, LPG Gas Distribution in Pidie Regency.